Dialogic data innovations for sustainability transformations and flood resilience: the case for waterproofing data - Albuquerque, João Porto de; Anderson, Liana; Calvillo, Nerea; Cattino, Massimo; Clarke, Andrew; Cunha, Maria Alexandra; Degrossi, Lívia Castro; Garde-Hansen, Joanne; Klonner, Carolin; Lima-Silva, Fernanda; Marchezini, Victor; Martins, Mario Henrique da Mata; et al. (Global environmental change, 2023)
Extreme weather events are becoming more frequent and have increasing impacts, which disproportionately affect marginalised and impoverished communities. This article proposes and assesses a new methodological approach for developing innovative solutions based on urban data analytics to address sustainability challenges in light of changing climate conditions. ...
Online veröffentlicht am 27. Juli 2023
Gesehen am 07.12.2023